Radical Incrementalism in Action Through Institutional Work: Case Studies of Embedded Research in South Africa - Swilling, Mark; Huang, Ying-Syuan (Elaine); Mogosetsi-Gabriel, Nontsikelelo; Rathupetsane, Alboricah; Ndovela, Mlondi; Jezi, Priscilla; Malan, Garth; Tshangela, Mapula (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Sustainability researchers and non-academic actors are working more closely than ever to drive deep structural transformation toward just and sustainable futures. This paper illustrates how embedded researchers in South Africa navigate the political nature of institutional spaces through transdisciplinary action research. We propose radical incrementalism as a guiding philosophy and analyse seven cases using a collaborative autoethnographic approach. The analysis identifies four strategic choices: whether to embed, how to engage critically, when to maintain distance, and how to sustain long-term commitment. These insights illuminate the ethical and political complexities of shaping—or failing to influence—policy change within government institutions.